GROUP SO(4,2) AND SYMMETRY PROPERTIES OF D.I. MENDELEEV'S PERIODIC SYSTEM ELEMENTS - A. L. Gurskii; L. I. Hurski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The group-based method of classification of chemical elements for definition of their place in the Mendeleev’s periodic system of elements is considered. The arrangement of energetic elements in periods according to the diagram of experimentally defined atomic electron shells is compared to energy levels of elements estimated from the Madelung-Klechkovsky lexicographic ordering rules. It is shown that for adequate description of the set of elements in the framework of approach based on the use of the group method, the changig the peculiarirties of the eigenvalues degeneration of the electron hamiltonian describing a hydrogen-like system is necessary. For this, it is sufficient to include into the hamiltonian a term containing operator of squared orbital momentum.